Studies on the application of N, N-bis(phosphonomethyl)-sulfamic acid in the selective flotation separation of pyrite from serpentine. (15th June 2022) - Zhang, Xu-Gang; Zhang, Jie; Ye, Wen-long; Pan, Cheng-Lin; Wei, Xiang-Xiang; Hu, Xiu-Qin; Luo, Yong-Chun; Xu, Peng-Fei
Graphical abstract: Highlights: SABMP adsorbs on the minerals surface but it can't depress the floatability of serpentine and pyrite, respectively. SABMP can effectively eliminate the adverse effect of serpentine on pyrite flotation. The surface charge of serpentine is changed from positive to negative in the presence of SABMP. SABMP can not only absorb on the surface of serpentine but also accelerate the dissolution of Mg 2+ on serpentine surface. Abstract: The flotation of pyrite is often depressed by the slime coating of fine serpentine. To eliminate the negative effect of serpentine, N, N-bis(phosphonomethyl)-sulfamic acid (SABMP) was employed as the depressant in this study. The results of micro-flotation experiments showed that the addition of SABMP could significantly reduce the adverse effect of fine serpentine and restore the floatability of pyrite in the pyrite-serpentine system. However, the floatability of pyrite and serpentine had not been obviously reduced in single mineral flotation after the addition of SABMP. The adsorption and ICP results indicated that SABMP could be adsorbed on serpentine surface and simultaneously promote the dissolution of Mg ions on serpentine surface. Further XPS tests demonstrated that SABMP interacted with the Mg species exposed on the surface of serpentine. In addition, it was discovered that the addition of SABMP changed the zeta potential of serpentine from positive to negative at pH 8.5, which eliminated the hetero-coagulation between pyrite and serpentine. The turbidity test further suggested that SABMP could convert the aggregation to the dispersion between pyrite and serpentine. These results demonstrated that SABMP is a potential depressant in the selective flotation separation of pyrite from serpentine.